Lamin B1 as a key modulator of the developing and aging brain - Koufi, Foteini-Dionysia; Neri, Irene; Ramazzotti, Giulia; Rusciano, Isabella; Mongiorgi, Sara; Marvi, Maria Vittoria; Fazio, Antonietta; Shin, Minkyung; Kosodo, Yoichi; Cani, Ilaria; Giorgio, Elisa; Cortelli, Pietro; et al. (Frontiers in Cellular Neuroscience, 2023)
Lamin B1 is an essential protein of the nuclear lamina that plays a crucial role in nuclear function and organization. It has been demonstrated that lamin B1 is essential for organogenesis and particularly brain development. The important role of lamin B1 in physiological brain development and aging has only recently been at the epicenter of attention and is yet to be fully elucidated. Regarding the development of brain, glial cells that have long been considered as supporting cells to neurons have overturned this representation and current findings have displayed their active roles in neurogenesis and cerebral development. Although lamin B1 has increased levels during the differentiation of the brain cells, during aging these levels drop leading to senescent phenotypes and inciting neurodegenerative disorders such as Alzheimer's and Parkinson's disease. On the other hand, overexpression of lamin B1 leads to the adult-onset neurodegenerative disease known as Autosomal Dominant Leukodystrophy. This review aims at highlighting the importance of balancing lamin B1 levels in glial cells and neurons from brain development to aging.